2018
DOI: 10.3390/polym10070775
|View full text |Cite
|
Sign up to set email alerts
|

Chain Trajectory, Chain Packing, and Molecular Dynamics of Semicrystalline Polymers as Studied by Solid-State NMR

Abstract: Chain-level structure of semicrystalline polymers in melt-and solution-grown crystals has been debated over the past half century. Recently, 13 C-13 C double quantum (DQ) Nuclear Magnetic Resonance (NMR) spectroscopy has been successfully applied to investigate chain-folding (CF) structure and packing structure of 13 C enriched polymers after solution and melt crystallization. We review recent NMR studies for (i) packing structure, (ii) chain trajectory, (iii) conformation of the folded chains, (iv) nucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
(230 reference statements)
0
9
0
Order By: Relevance
“…For example, most PEO/Li + complexes are semi-crystalline [23]. In semi-crystalline polymers, the crystallites are always surrounded by non-crystalline structures [24][25][26]. Such morphologies are also present in most PEO/Li + complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most PEO/Li + complexes are semi-crystalline [23]. In semi-crystalline polymers, the crystallites are always surrounded by non-crystalline structures [24][25][26]. Such morphologies are also present in most PEO/Li + complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer crystallization is a dynamic process of reorganizing the random coil chain to a folded chain, a motif conformation in lamellar polymer crystals. Quantifying chain folding is particularly important for the disclosure of the kinetic mechanism of polymer crystallization at the molecular level as well as the development of advanced polymer materials . Various techniques, including neutron scattering (NS), infrared (IR) spectroscopy, , transmission electron microscopy (TEM), solid-state NMR, and theoretical simulations, have been employed to characterize the chain folding. However, the quantification of the chain folding is quite challenging, and the results are quite inconsistent.…”
mentioning
confidence: 99%
“…Chain fold is a basic feature of polymer crystallization [23,24]. In the past few years, a lot of studies have been done on polymer fold [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Chain fold is a basic feature of polymer crystallization [23,24]. In the past few years, a lot of studies have been done on polymer fold [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Ungar et al [25,26] studied on the monodisperse polymers and showed more information about polymer crystallization, such as integer folding, non-integer folding, lamellar thickening and the nature of fold surface and end surface.…”
Section: Introductionmentioning
confidence: 99%